2016
DOI: 10.1177/0003319716637516
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Heart-Type Fatty Acid-Binding Protein and Myocardial Performance Index for Early Detection of 5-Fluorouracil Cardiotoxicity

Abstract: In the present study, we aimed to evaluate temporal changes in heart-type fatty acid-binding protein (h-FABP) and myocardial performance index (Tei index) following administration of 5-fluorouracil (5-FU), a chemotherapeutic agent associated with myocardial ischemia induced by coronary vasospasm. Thirty-two patients with cancer receiving their first 5-FU-based chemotherapy were included in the study. Prior to chemotherapy and 24 hours after the initiation of chemotherapy, all patients underwent a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
(22 reference statements)
0
17
0
1
Order By: Relevance
“…In clinical patients, angiographic examinations of the coronary arteries have shown that CAS particularly occurs in cases of variant or unstable angina [ 4 , 6 , 7 ]. Heart-type fatty acid-binding protein (h-FABP) and myocardial performance index (Tei index) have recently been proposed to be useful for early detection of ischemia coronary vasospasm induced by 5- Fluorouracil [ 8 ]. At forensic autopsies, the pathological diagnosis of antemortem CAS is difficult due to limitation of specific markers.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical patients, angiographic examinations of the coronary arteries have shown that CAS particularly occurs in cases of variant or unstable angina [ 4 , 6 , 7 ]. Heart-type fatty acid-binding protein (h-FABP) and myocardial performance index (Tei index) have recently been proposed to be useful for early detection of ischemia coronary vasospasm induced by 5- Fluorouracil [ 8 ]. At forensic autopsies, the pathological diagnosis of antemortem CAS is difficult due to limitation of specific markers.…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to lack of power but may also suggest that myocyte injury is uncommon and only occurs in severe cases of cardiotoxicity. Prior studies of troponin levels during 5-FU treatment have shown comparable findings, with no change in troponin during treatment [17][18][19][20][21]. However, the number of patients included in the individual studies of troponin levels during 5-FU treatment was small (n = 22-59).…”
Section: Discussionmentioning
confidence: 90%
“…Relationship between a positive fluid balance when in intensive care unit and possible development of postoperative period complications (A) and atrial fibrillation (B) in patients after coronary artery bypass grafting on a beating heart фузионная программа при недооценке диастолической дисфункции ЛЖ сопровождается повышением гид-робаланса в раннем послеоперационном периоде, что приводит к осложненному течению послеоперацион-ного периода, в том числе пароксизмам фибрилляции предсердий. Индекс производительности миокарда изучается у пациентов с коронарной патологией и пороками сер-дца; он используется для оценки кардиотоксичности при химиотерапии [22], выявлении дисфункции мио-карда при сахарном диабете [23], а также полезен при трансплантации сердца как до операции, так и при диагностике отторжения трансплантата [24]. Нами об-наружена взаимосвязь Tei-индекса с vTIвтлж как сурро-гатным показателем ударного объема, иными словами, повышение производительности миокарда приводит к повышению ударного объема и, следовательно, сер-дечного выброса.…”
Section: Discussionunclassified